2004
DOI: 10.1177/146144804044330
|View full text |Cite
|
Sign up to set email alerts
|

Self-Presentation of Small Developing Countries on the World Wide Web: A Study of Official Websites

Abstract: The author analyzes the official national websites of small developing countries for content and function. The surveyed websites are found to emphasize geographical, tourism and identifying information about the small states but contain little in terms of investment information, suggesting that the web is seen as a tool of self-promotion but is not equally perceived as a tool for attracting investment. A positive relationship is observed between literacy and the range of national websites published for each su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 27 publications
0
7
0
3
Order By: Relevance
“…In a study of small developing countries, Mohammed (2004) found that 84% had official government websites. In addition, 35% of the official government websites analyzed were tourism promotion vehicles with a strong emphasis on selfpresentation.…”
Section: Tourist Destination Image-formationmentioning
confidence: 98%
“…In a study of small developing countries, Mohammed (2004) found that 84% had official government websites. In addition, 35% of the official government websites analyzed were tourism promotion vehicles with a strong emphasis on selfpresentation.…”
Section: Tourist Destination Image-formationmentioning
confidence: 98%
“…More recently, the internet has become a major platform to promote destinations, through the use of stimulating visuals that enhance a user's travel intentions (Fürsich and Robins 2002;2004;Kaplanidou and Vogt 2006). Consequently, tourism destination websites have become one of the main information sources for users to identify destinations that relate to their needs, motivation, and self-image (Frías, Rodríguez, and Castañeda 2008).…”
Section: Hypothesesmentioning
confidence: 99%
“…The design of a destination site is critical in providing a look and feel of the place online (Govers and Go 2005, Govers, Go and Kumar 2007a; 2007b). Thus, the site’s design has a great impact on the symbolic image that individuals develop of the destination (Mohammed 2004; Lepp, Gibson, and Lane 2011). When cultural markers and cultural values are localized, the site is purposely tailored to become culturally congruent with its target market.…”
Section: Studymentioning
confidence: 99%
“…This could be motivated by the different history, sociopolitical and socio-cultural conditions of Indonesia and the Baltic countries. The predominant occurrences of the "positive self-presentation" on the verbal texts reflect the nature of the tourism website as an advertising genre (Michelson & Valencia, 2016) and as a means to control impressions (Dominick, 1999) and to present a country to the international community (Mohammed, 2004). Thus, as a promotional medium, it uses words representing positive images of Indonesia as a world-class tourism destination.…”
Section: National Identity Construction and Promotion Through Verbal Textsmentioning
confidence: 99%